METHODOLOGY OF POPULARIZATION OF ADVANCED PEDAGOGICAL EXPERIENCES IN FINE ARTS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Currently, there are various opinions, views, and approaches to teaching based on advanced pedagogical technologies. This is not accidental, of course. The constant search for establishing teaching based on modern, advanced pedagogical technologies, creating understandable and interesting areas of the educational process for students remains an important task of the teacher. This article discusses what a teacher should follow when designing lessons on pedagogical technology, and the existence of three main approaches to advanced pedagogical experience.